Exploring the spatiotemporal evolution of bioenergy with carbon capture and storage and decarbonization of oil refineries with a national energy system model of Colombia - Ahmed Younis; Tjerk Lap; Edgar Yáñez; Lorena Suarez Bermudez; René Benders; André Faaij (Energy Strategy Reviews, 2023)
Bioenergy combined with carbon capture and storage (BECCS) has a high mitigation potential of greenhouse gases in the energy system. However, the feasibility of its deployment depends on co–location of suitable storage basins and biomass resources with low-carbon stocks. Moreover, national transition analyses towards low–carbon energy systems have often given little attention to the mitigation potential of existing oil refineries, which are major components of current energy systems. We parametrized and incorporated these knowledge gaps into an energy system optimization model and used it analyze mitigation pathways towards carbon neutrality of the Colombian energy system by midcentury.Our results show that modern bioenergy could contribute 0.8–0.9 EJ/y (48–51 %) to the final energy consumption by 2050 at a system cost of 29–35 B$/y. BECCS value chains could deliver a mitigation potential of 37–41 % of the cumulative avoided emissions between 2030 and 2050. Low–carbon retrofitting of existing oil refineries could contribute up to 19 % of the total biofuel production and 10 % of the total CO2 capture by 2050. The Andes and Caribbean could be promising regions for BECCS because of their high potential for biomass supply and carbon sinks. In contrast, Orinoquía has a high potential for bioenergy and more uncertainty of CCS, depending on the access to nearby carbon sinks.This framework could be used to harmonize between the visions of the energy and agricultural sectors, national government and the oil sector, and national and regional governments, towards integrated planning for low-carbon development.